2023
DOI: 10.9734/ijpss/2023/v35i102927
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Targeted Yield Equations for Finger Millet under Southern Dry Zone of Karnataka

Abstract: General usage of fertilizers resulted in less productive soils and not being able to harvest the complete genetic potential of the crop. Hence, it’s indispensable to follow a more scientific application of fertilizer nutrients i.e, Soil Test Crop Response (STCR) approach to meet the nutrient demand of the crop and to feed the increasing human population without compromising on limited land resources. Therefore, field experiments were carried out at Mandya and Mysore to validate the fertilizer prescription equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Bhatt et al [8] observed that the targeted yield model for brinjal was better than the general recommendations in terms of net savings on fertilizers. Recently, Murthy et al [9] concluded that the targeted yield equation approach was the most suitable and effective approach for fertilizer recommendation for finger millet crop. Eunice et al [10] while generating targeted yield equations for the amaranthus crop concluded that fertilizer and manure recommendations based on STCR (Soil Test Crop Response)targeted yield equations not only improved crop yield but also improved the soil quality.…”
Section: Introductionmentioning
confidence: 99%
“…Bhatt et al [8] observed that the targeted yield model for brinjal was better than the general recommendations in terms of net savings on fertilizers. Recently, Murthy et al [9] concluded that the targeted yield equation approach was the most suitable and effective approach for fertilizer recommendation for finger millet crop. Eunice et al [10] while generating targeted yield equations for the amaranthus crop concluded that fertilizer and manure recommendations based on STCR (Soil Test Crop Response)targeted yield equations not only improved crop yield but also improved the soil quality.…”
Section: Introductionmentioning
confidence: 99%